Research on pairing-free certificateless batch anonymous authentication scheme for VANET - Cheng SONG; Ming-yue ZHANG; Wei-ping PENG; Zong-pu JIA; Zhi-zhong LIU; Xi-xi YAN (Tongxin xuebao)
To solve the problem of security and efficiency of anonymous authentication in vehicular ad hoc network,a pairing-free certificateless batch anonymous authentication scheme was proposed.The public and private keys and pseudonyms were jointly generated by the trusted third party and vehicle,so the system security didn't depend on the tamper device.The scheme can realize authentication,anonymity,traceability,unforgeability,forward or backward security,and so on.Furthermore,under the random oracle model,the scheme can resist Type I and Type II attacks.Because there is no need to use certificates during authentication,the system storage load is effectively reduced.At the same time,the scheme realizes the batch message authentication on the basis of pairing-free operation,so the authentication efficiency is improved.Therefore,the scheme has important theoretical significance and application value in the resource-limited internet of things or embedded environment.